ChemInform Abstract: A New Organocatalyst Derived from Abietic Acid and 4‐Hydroxy‐L‐proline for Direct Asymmetric Aldol Reactions in Aqueous Media. Issue 12 (March 2015) - Bhowmick, Sudipto; Kunte, Sunita S.; Bhowmick, Kartick C.
Abstract The new catalyst efficiently catalyzes the aldol reaction between aromatic aldehydes and ketones with only 1 mol% loading.